In vivo bronchial epithelial interferon responses are augmented in asthma on day 4 following experimental rhinovirus infection. Issue 9 (5th July 2022) - Farne, Hugo; Lin, Lijing; Jackson, David J; Rattray, Magnus; Simpson, Angela; Custovic, Adnan; Joshi, Shilpy; Wilson, Paul A; Williamson, Rick; Edwards, Michael R; Singanayagam, Aran; Johnston, Sebastian L
Abstract : Despite good evidence of impaired innate antiviral responses in asthma, trials of inhaled interferon-β given during exacerbations showed only modest benefits in moderate/severe asthma. Using human experimental rhinovirus infection, we observe robust in vivo induction of bronchial epithelial interferon response genes 4 days after virus inoculation in 25 subjects with asthma but not 11 control subjects. This signature correlated with virus loads and lower respiratory symptoms. Our data indicate that the in vivo innate antiviral response is dysregulated in asthma and open up the potential that prophylactic rather than therapeutic interferon therapy may have greater clinical benefit.